From school dorms to youtube, facebook and whatsapp: the multifacets of bullying in a digital environment - Abdul Jalil, Juriah; Daud, Mahyuddin (LEXIS NEXIS, 2016)
School bullying usually occurs within a school vicinity. As technology develops, particularly smartphones with recording mechanisms and access to internet, video recordings of incidents could be uploaded on YouTube and/or disseminated through WhatsApp and social media. These videos could be viewed by many people at a time and passed on or shared with other members or group within clusters of social networks and private networks with just a click or a touch. Each time a video is shared, the incident is replayed and relayed, thus may create a chain of continuous bullying on the net by the sharers. Reasons for uploading and sharing of the video may vary, but the act of doing so may amount to cyberbullying. This article aims to investigate whether the act of uploading, disseminating and sharing of such video amounts to cyberbullying; the impact on victims, bullies and society; what legal mechanism could be adopted to ensure deterrence of such abuse on the internet. The study is based on doctrinal and statutory analysis of selected jurisdiction and will analyse especially, the legal approach in other jurisdiction as potential solutions. The act of uploading, disseminating and sharing of the impugned video may amount to cyberbullying if it is accompanied with the intention to harass, humiliate and embarrass the parties in the video. The act can have significant impact on both bullies and victims and such act could be deterred by s 211 of the Communication and Multimedia Act 1998; the requirement to give information relating to a crime under s 13 of the Criminal Procedure Code; and liability under the bad Samaritan law or moral obligation to report.